PENGARUH DOSIS PHONSKA TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS BAWANG MERAH PADA MUSIM HUJAN - Rajiman, Rajiman (Jurnal Ilmu-Ilmu Pertanian, 2015)
This research were aimed 1) to study the effected phonska dosage to growth and yield of shallot in rainy season, 2) to study the effected varieties to growth and yield of shallot in rainy season. The research was implemented at Berbah, Sleman for February April 2015. The research used design of split-plots by 3 replication. The main plot was phonska doses (P) i.e P1= 100 kg/ha, P2= 200 kg/ha, P3= 300 kg/ha dan P4 = 400 kg/ha. The sub plot were varieties (V) i.e V1 = Bima, V2 = Tiron, V3 = Crok Kuning. Observation was conducted to plant height, leaves number, fresh weight per cluster, dry weight per cluster, Stover weight per hectare, fresh bulb weight per hectare, dry bulb weight per hectare, bulb diameter and harvest index. The data obtained was analysed by variance analysis with 5% level of significance. The results of research showed that didn't interaction to phonska dosage and varieties to all parameters. The increasing phonska dosage didn't affected significantly to all growth and yield of shallot. Varieties affected significantly to growth and yield the shallot. The highest productivity in rainy season was Tiron varieties i e. fresh bulb weight per hectare (107,1 kw/ha) dan dry bulb weight per hectare (96,7 kw/ha).